Investigating the Impact of Personal Branding on Identity Representation Through Bibliometric Analysis: Menyelidiki Dampak Personal Branding terhadap Representasi Identitas Melalui Analisis Bibliometrik - Safaras, Syahmi; Rositah, Nila Dwi Noor; Safira, Tazkiyah Azmi; Abadi , Totok Wahyu; Usaifani, Nuris Shofa (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the impact of personal branding on identity representation using bibliometric analysis. By reviewing numerous articles from Google Scholar and analyzing data with VOSviewer and Publish or Perish (Crossref) software, the research identifies key themes and keywords related to personal branding, identity, and social media. The analysis of 1,000 journals from 2013–2023 reveals interconnected authors and significant terms, with newer research trends highlighted. The findings demonstrate the effectiveness of bibliometric tools in mapping research themes and identifying influential authors and keywords in the field. Highlights: Impact of Personal Branding: Examines how personal branding affects identity representation. Bibliometric Tools: Utilizes VOSviewer and Publish or Perish for comprehensive data analysis. Research Trends: Identifies key authors, keywords, and emerging trends from 2013-2023. Keywords: Personal Branding, Identity Representation, Bibliometric Analysis, Social Media, Vosviewer